Short-chain fatty acids and regulation of pancreatic endocrine secretion in mice. Issue 5 (3rd September 2019) - Ørgaard, Anne; Jepsen, Sara Lind; Holst, Jens Juul
ABSTRACT: The intestinal microbiota has been demonstrated to influence host metabolism, and has been proposed to affect the development of obesity and type 2 diabetes (T2D), possibly through short-chain fatty acids (SCFAs) produced by fermentation of dietary fiber. There are some indications that SCFAs inhibit glucose-stimulated insulin secretion (GSIS) in rodents, but research on this subject is sparse. However, it has been reported that receptors for SCFAs, free fatty acid receptor 2 (FFAR2) and FFAR3 are expressed not only on gut endocrine cells secreting GLP-1 and PYY, but also on pancreatic islet cells. We hypothesized that SCFAs might influence the endocrine secretion from pancreatic islets similar to their effects on the enteroendocrine cells. We studied this using isolated perfused mouse pancreas which responded adequately to changes in glucose and to infusions of arginine. None of the SCFAs, acetate, propionate and butyrate, influenced glucagon secretion, whereas they had weak inhibitory effects on somatostatin and insulin secretion. Infusions of two specific agonists of FFAR2 and FFAR3, CFMB and Compound 4, respectively, did not influence the pancreatic secretion of insulin and glucagon, whereas both induced strong increases in the secretion of somatostatin. In conclusion, the small effects of acetate, propionate and butyrate we observed here may not be physiologically relevant, but the effects of CFMB and Compound 4 on somatostatin secretion suggest that it may be possible to manipulate pancreatic secretion pharmacologically with agonists of the FFAR2 and 3 receptors, a finding which deserves further investigation.